I am David - Feig, Paul (Interactive Digital Entertainment.)
" I Am David" is adapted from Anne Holm's internationally acclaimed novel North to Freedom. It is the story of a 12-year- old boy, David (Ben Tibber), who escapes a Communist concentration camp with little more than a compass, a sealed letter, a loaf of bread, and instructions to carry the letter to Copanhagen, Ddenmark. David is thrust into the free world for the first time in his young life as he travels across Europe. It is a spiritual voyage of discovery, where David Slowly loses his instinctual mistrust of humanity and begins to smile, share trust and ultimately, love. " I Am David" addresses the cruelties, politics and suffering of warfare while celebrating the resilience of youth and the unbreakable spirit of a child.